Enrichment of Incompatible Elements in Alkaline Syenites in Large Igneous Provinces Due to Magma Replenishment and Reactive Porous Flow in a Mush Reservoir. (11th January 2023) - Zhu, Sheng-Zhu; Huang, Xiao-Long; Yu, Yang; Yang, Fan; Wang, Christina Yan; He, Peng-Li; Cao, Jun
Abstract: Understanding the petrogenesis of alkaline syenites is important for constraining the mechanisms of rare earth element (REE) and rare-metal mineralization. Here we report a detailed petrological and geochemical study of early Permian syenitic rocks from the southwestern Tarim large igneous province (TLIP) in the Wajilitag area (China). We use these data to investigate the complex magmatic processes responsible for the enrichment of incompatible elements (e.g. REEs and rare metals) in these rocks. The Wajilitag syenitic rocks comprise early hornblende syenite (281 Ma) and later nepheline syenite (278 Ma), both of which are spatially and temporally associated with mafic intrusions (i.e. gabbro and diabase). These syenitic rocks show continuous variations in major elements with the mafic rocks. They also have similar Sr–Nd–Hf isotopic compositions with the nearby mafic rocks, denoting that the Wajilitag syenitic rocks should be derived from the melts represented by these mafic rocks. However, these syenitic rocks, particularly the nepheline syenites, are typically characterized by extreme enrichment of incompatible elements, which is hard to be accounted by simple fractional crystallization of mafic magmas. Some clinopyroxene phenocrysts in the Wajilitag nepheline syenites show oscillatory zoning with strikingly increasing and then gradually decreasing MgO contents, which recorded replenishment of mafic magma at the interval. Low-MgO clinopyroxene mantles and/or rims have much higher incompatible element contents (e.g. Nb, Ce, and Zr) and ratios (e.g. Ce/Y) than their cores, which could reflect melt injection controlled by reactive porous flow in a mush reservoir of a crustal magma chamber. Such processes may also cause the high Ce and/or Nb contents of the mantles and/or rims of zoned titanite and apatite phenocrysts. The injection of reactive porous flow melts is the key process that produces the extreme enrichment of incompatible elements in the alkaline syenites from the western TLIP, as well as other plume-related alkaline syenites that host world-class REE and rare-metal deposits.